Transcatheter Mitral Valve Replacement With a Novel Dual Stent Bioprosthesis. (June 2017) - Moore, Benjamin M.; Ng, H.K. Bernard; Naoum, Christopher; Simmons, Lisa; Cartwright, Bruce L.; Wilson, Michael K.; Ng, Martin K.C.
Abstract : Supplemental Digital Content is available in the text.